Histórias de infâncias na rua: uma narrativa entre violações de direitos e proteção da vida. - Lima Júnior, Itamar Sousa (2019)
This research aimed to understand the experience of the street situation of children and adolescents in the city of Recife. It is a qualitative research, with a phenomeno- logical basis of the type research intervention. The research was carried out in a Civil Society Organization of reference in the socio-educational work with street children and adolescents in the municipality. Participating in this process were 9 children and adolescents of both sexes, being 7 boys and 2 girls, aged between 11 and 17 years, all with more than one year in a street situation. As a research instrument were adopted participant observation, reflective interview and logbooks. From the narratives col- lected from the logbooks and the reports of the meetings and the reflective interview, great themes emerged that were constituted in what we will call constellations: Extreme Poverty, Violence, Protection Isles, Play in the street: the ludic and danger, At some point will be cried for it, My life is a hell and False freedom. Such constellations illumi- nated by the reflections of Hannah Arendt enabled, in addition to a greater understand- ing of the experience of these boys’ and girls’ indications of ways to new ways of acting with this public. Thus, the human conditions that constitute the phenomenon of the street situation, such as extreme poverty and violence, have highlighted the violations of this group, but it was also possible to understand the need for protection that is claimed by these children and adolescents and compels to a political activity that deals with the love to the world.